Prevalence Of Under﻿nutrition And Associated Factors Among Adults Receiving First-Line Antiretroviral Treatment In Public Health Facilities Of Arba Minch Town, Southern Ethiopia - Oumer, Bilcha (HIV AIDS (Auckl), 2019)
INTRODUCTION: Access to antiretroviral drugs for all infected persons in need is a global health priority. The primary goals of initiating antiretroviral drugs are to suppress human immunodeficiency virus viral replication and to restore immune function. However, adequate nutrition is necessary to manage opportunistic infections and to maintain the immune system. Therefore, this study aimed to determine the recent prevalence of undernutrition and associated factors among HIV patients receiving first-line antiretroviral therapy in public health facilities of Arba Minch town, Gamo zone, Southern Ethiopia. METHODS: Institution-based cross-sectional study was used among 333 adult patients receiving first-line antiretroviral therapy at public health facilities of Arba Minch town. A simple random sampling technique was used to select the study subjects. Data were collected through interviewer-administered questionnaires. Binary and multivariable logistic regression analyses were used to identify factors associated with undernutrition. A p-value <0.05 with a 95% confidence level was used to declare statistical significance. RESULTS: The overall prevalence of undernutrition among adult patients receiving first-line antiretroviral therapy is 23.72% (95% CI: 19.13–28.27%). Current substance use (AOR=1.83, 95% CI:1.09–3.08), duration on antiretroviral therapy (AOR=1.87, 95% CI:1.06–3.30), not taking cotrimoxazole preventive therapy (AOR=2.09, 95% CI:1.15–3.82), advanced WHO clinical stages (AOR=5.1, 95% CI: 2.9–7.7), CD4 count less than 350 cell/mm(3) (AOR=1.83, 95% CI: 1.09–3.05) and active tuberculosis (AOR=1.89, 95% CI: 1.02–3.53) were factors significantly associated with undernutrition among respondents who were enrolled on first-line antiretroviral therapy. CONCLUSION: This study shows that the prevalence of undernutrition was high among adult patients on first-line antiretroviral therapy. Therefore, this finding shows the need to implement nutrition programs to improve the nutritional status of adults living with HIV in the study area. The interventions should emphasise those patients who use the substance, who are in advanced WHO clinical stage and have active tuberculosis. Besides, emphasis should be given for patients to undertake cotrimoxazole preventive therapy and to regularly follow their CD4 count.